Effects of Child Tax Benefits on Poverty and Labor Supply: Evidence from the Canada Child Benefit and Universal Child Care Benefit - Baker, Michael; Messacar, Derek; Stabile, Mark (Journal of Labor Economics, 2023)
We investigate how reforms of Canada’s child allowances affected household poverty and maternal employment—the 2015 increase and expansion of the Universal Child Care Benefit and the 2016 introduction of a new Canada Child Benefit (CCB). We document that both reforms reduced child poverty, although the CCB had greater effect. By 2018, we estimate that the CCB reduced poverty by 11% in families headed by a single mother and by nearly 17% in two-parent families. We find no evidence, on either the extensive or the intensive margin, of a negative labor supply response to either of the program reforms.